Improving the efficacy for meropenem therapy requires a high probability of target attainment in critically ill infants and children - Wang, Zeming; Bi, Jing; You, Dianping; Tang, Yu; Liu, Gang; Yu, Jinqian; Jin, Zhipeng; Jiang, Tingting; Tian, Xue; Qi, Hui; Dong, Lei; Dong, Lili; et al. (Frontiers in Pharmacology, 2022)
Probability of target attainment is the key factor influencing the outcome of meropenem therapy. The objective of the present study was to evaluate the relationship between the time in which the plasma free concentration of meropenem exceeds the minimum inhibitory concentration of pathogens (fT>MIC) during therapy and the clinical outcome of treatment to optimize meropenem therapy. Critically ill children with infections who had received intravenous meropenem monotherapy were included. The relationship between fT>MIC of meropenem and effectiveness and safety were explored. Data from 53 children (mean age ± standard deviation, 26 months ± 38) were available for final analysis. Children with fT>MIC ≥ 5.6 h (n = 14) had a more significant improvement in antibacterial efficacy in terms of decrease in fever (P = 0.02), white blood cell count (P = 0.014), and C-reactive protein (P = 0.02) compared with children with fT>MIC < 5.6 h (n = 39) after meropenem therapy completed. No drug-related adverse events were shown to have a causal association with meropenem therapy. Our study shows the clinical benefits of sufficient target attainment of meropenem therapy. Meeting a suitable pharmacodynamic target attainment of meropenem is required to ensure better antibacterial efficacy in critically ill infants and children.